PEREMPUAN SEBAGAI KEPALA KELUARGA PRESPEKTIF HUKUM ISLAM (STUDI KASUS DI KELURAHAN SUKOMULYO KECAMATAN LAMONGAN) - Alif Hadi Saifulloh; Fathurrahman Alfa; Dwi Ari Kurniawati (Jurnal Hikmatina, 2022)
Women as heads of families from the perspective of Islamic law. This research uses direct research located in the Sukomulyo Village. This type of research is direct, which aims to obtain a complex picture of reality and find patterns of interactive relationships. This research was conducted by describing and analyzing data expressed in the form of sentences or words, namely qualitative.The results of the research obtained are that women become heads of families not because of their own desires but are forced by circumstances, many factors are behind this case such as her husband has died, her husband doesn't want to work and doesn't even want to know about domestic life, and some are want to appreciate a form of ideals that have not been realized, on the other hand all these problems or problems certainly have an impact on children, such as children rarely getting a smile, not getting pocket money, and so on, according to Islamic law, activities that make women the head of the family are allowed as long as not leaving an obligation such as working outside with the husband's permission, working to cover the genitals and so on.